Self‐reported competences of public health nurses for developing needs‐oriented local healthcare plans: A nationwide cross‐sectional survey. (10th January 2021) - Yoshioka‐Maeda, Kyoko; Shiomi, Misa; Katayama, Takafumi; Hosoya, Noriko; Fujii, Hitoshi; Mayama, Tatsushi
Abstract: Aim: To identify self‐reported competencies of public health nurses for reflecting community healthcare needs in local healthcare plans. Design: We conducted a nationwide cross‐sectional survey in Japan from October 7‐November 30, 2019. Methods: We sent 2, 185 self‐reported questionnaires to public health nurses in Japan who had developed a local healthcare plan since 2013. Self‐reported questionnaires included questions regarding demographic data and the reflection of community healthcare needs in local healthcare plans, and the involvement in local healthcare planning. Results: We analysed 1, 042 questionnaires: 651 (62.5%) were from public health nurses who reported that they elicited and shared community views to be reflected for purposes of local healthcare planning (the reflecting group), and 391 (37.5%) of the remaining public health nurses who reported that they did not do so (the non‐reflecting group). The logistic regression analysis revealed that public health nurses in the reflecting group were more likely to be in a managerial position, have colleagues who played an active role in healthcare planning, conduct a questionnaire survey, engage in group work, participate in a municipal healthcare planning committee with community‐dwelling people, and identify the opinions of the professional organizations. Conclusions: Identifying community healthcare needs through collaboration with community‐dwelling people and professional organizations should be essential competencies for public health nurses (the reflecting group) in developing needs‐oriented local healthcare plans. Impact: Identification of their related competencies for developing a needs‐oriented local healthcare plan as an upstream strategy to mitigate the prevalence of health inequities in each community.